(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: This study aims to elucidate the association between the phenomena of nausea and vomiting during gestation and their potential impact on unfavorable maternal and neonatal outcomes specifically in the population of Pakistani women. METHODOLOGY: A longitudinal cohort investigation was undertaken over a duration of 24 months at a tertiary care facility in Karachi, involving the enrolment of 400 pregnant women in the first trimester exhibiting viable pregnancies. Participants were stratified according to their Pregnancy-Unique Quantification of Emesis (PUQE) scores into cohorts categorized as exposed (NVP) and unexposed. The detailed recording and analysis of the health results for mothers and their babies were done using SPSS version 26.0, where a p-value ≤ 0.05 was considered as statistically significant. RESULTS: A thorough examination involving 400 participants revealed that the exposed group (n=200) had a notably younger average age (28.82 ± 4.65 years against 29.89 ± 4.31 years), a decreased body mass index (26.71 ± 4.52 compared with 27.28 ± 4.47), and elevated PUQE scores (9.25 ± 2.05 in contrast to 4.45 ± 1.34). No statistically significant discrepancies were observed in the prevalence of preterm labor (9.0% versus 8.0%; relative risk: 1.065; p=0.720), cesarean section births (39.0% compared to 42.0%; p=0.541), or admissions to the Neonatal Intensive Care Unit (NICU) (8.5% versus 8.0%; p=0.856). The incidence of fetal growth restriction was found to be more pronounced in the exposed subgroup (11.5% v/s 6.5%; p=0.778). CONCLUSION: This research elucidates that NVP, although correlated with diminished maternal age and elevated PUQE scores, did not reveal statistically significant association with detrimental maternal outcomes such as preterm labor, antepartum hemorrhage, or delivery method. Similarly, neonatal outcomes including growth restriction, NICU admission, Apgar scores, and birth weight showed no difference among the groups. These results imply that moderate NVP may not serve as an independent predictor of adverse pregnancy or neonatal outcomes.